Abridged design with demand conventions for health care applications. (September 2022) - Teekaraman, Yuvaraja; Manoharan, Hariprasath; Kirpichnikova, Irina; Kuppusamy, Ramya
Abstract: This article focuses on the process of improving health care in real-time experimental settings. Despite the fact that there are numerous solutions for health-care issues, no remote solution has been devised. As a result, a novel model has been devised in the suggested technique, in which all hospital administration processes are simplified through the use of a virtual representation digital twin process. When such technologies are used, a discrete protocol is followed, resulting in the identification and integration of a security model based on demand movement. A machine learning discriminant analysis has been combined with the process of digital twin functions efficiently based on input signals and state vectors. The cohesive model is put to the test in four case studies, including delay monitoring, predictive score analysis, communication units, and battery charge rate, with all case study outcomes proving to be more effective than existing systems by an average of 74%. Graphical abstract: Image, graphical abstract